Mycobacterium tuberculosis Infection Drives Mitochondria-Biased Dysregulation of Host Transfer RNA–Derived Fragments. (22nd September 2020) - Looney, Monika M; Lu, Yin; Karakousis, Petros C; Halushka, Marc K
Abstract: Background: Mycobacterium tuberculosis ( Mtb ), the bacterium that causes tuberculosis, causes 10 million infections and 1.5 million deaths per year worldwide. The success of Mtb as a human pathogen is directly related to its ability to suppress host responses, which are critical for clearing intracellular pathogens. Emerging evidence suggests that key response pathways may be regulated by a novel class of small noncoding RNA, called transfer RNA (tRNA)–derived fragments (tRFs). tRFs can complex with Argonaute proteins to target and degrade messenger RNA targets, similarly to micro RNAs, but have thus far been overlooked in the context of bacterial infections. Methods: We generated a novel miRge2.0-based tRF-analysis tool, tRFcluster, and used it to analyze independently generated and publicly available RNA-sequencing datasets to assess tRF dysregulation in host cells following infection with Mtb and other intracellular bacterial pathogens. Results: We found that Mtb and Listeria monocytogenes drive dramatic tRF dysregulation, whereas other bacterial pathogens do not. Interestingly, Mtb infection uniquely increased the expression of mitochondria-derived tRFs rather than genomic-derived tRFs, suggesting an association with mitochondrial damage in Mtb infection. Conclusions: tRFs are dysregulated in some, but not all, bacterial infections. Biased dysregulation of mitochondria-derived tRFs in Mtb infection suggests a link between mitochondrial distress and tRF production. Abstract : tRNA-derived fragments (tRFs) are dysregulated by intracellular bacterial infection. While tRFs can derive from the nuclear or mitochondrial genomes of infected cells, only Mycobacterium tuberculosis biases mitochondria-derived tRF production, suggesting unique mitochondrial distress during M. tuberculosis infection.